Implementasi Metode Permainan Susun Kata dan Susun Kalimat (Suka-Suka) untuk Meningkatkan Penguasaan Mufrodat Siswa Kelas X MA Darul Huda Gumukmas - BIN NAFSAH, NOR HOLIS; Kuni Hamidah (Al-Kafaah : Journal of Arabic Language and Linguistics Education (ALLE), 2024)
In learning a language, such as Arabic, mastery of mufrodat is the main key in supporting good language skills. However, for maximum results in mastering mufrodat, it is necessary to use the right method. And one method that can be realized is the " Suka Suka " game method or arranging words and constructing sentences. This research aims to explain the process of implementing the "Suka Suka" game method to improve the mastery of Mufrodaat for Class X MA Darul Huda Bagorejo Gumukmas students. This research uses qualitative methods with data collection techniques through observation and documentation. Once collected, the data is analyzed and described, then concluded. The results of the research show that the application of the "Suka Suka" Game Method in Improving Mufrodat Mastery of Class their interest in learning Arabic.